Growth Response of White Shrimp (Litopenaeus vannamei) to Stocking Density Variations in Traditional System - Muhammad Javierrevo Aironic; Andi Rahmad Rahim; Aminin Aminin (Jurnal Biologi Tropis, 2026)
Vannamei shrimp (Litopenaeus vannamei) cultivation is one of the fisheries sub-sectors that has high economic value and is important in supporting the economy, among various cultivation systems, traditional ponds are still the choice for most farmers, especially those who have limited capital and supporting technology. This study aims to analyze the weight growth and absolute weight growth rate of vannamei shrimp cultivated in traditional ponds, this study was carried out for 35 days, the variables of this study include the absolute weight and absolute length of the cultivated shrimp. This study shows that shrimp in pond A have better growth than pond B, where the absolute weight is 15.92 grams while in pond B it is 7.56 grams. Analysis of the absolute length growth of vannamei also shows better in pond A with a value of 5.73 cm while in pond B it is 2.90 cm. Density and water quality are the causes of slow growth, on the other hand, land area, optimal density is more profitable for shrimp in obtaining natural food.